A new species of rock-dwelling gecko (Gekkonidae: Gehyra) from the Mt Surprise region of northern Queensland, Australia - Zozaya, Stephen M.; Fenker, Jéssica; Macdonald, Stewart L. (Zootaxa, 2019)
We describe a new species of rock-dwelling Gehyra Gray, 1834 (Gekkonidae) from the Einasleigh Uplands of inland north Queensland, Australia. Morphological, ecological, and molecular data clearly support the new species as distinct and place it within the ‘australis group’. Gehyra electrum sp. nov. is distinguished from congeners by a combination of medium adult size (SVL 46–50 mm), an orange-brown to pinkish-orange background colouration with a pattern of distinct whitish spots and irregular black to purple-brown blotches or bars, possessing 7–8 undivided subdigital lamellae on the expanded portion of the fourth toe, and a wedge-shaped mental scale that separates the inner-postmental scales along 40% or more of their length. Gehyra electrum sp. nov. is a rock specialist currently known only from granite outcrops of the Mt Surprise region, Queensland. This is the second recently described Gehyra from the Einasleigh Uplands and adds to the growing number of endemic reptiles recognised in the region.